Effects of Line and Pillar Array Microengineered SiO2 Thin Films on the Osteogenic Differentiation of Human Bone Marrow-Derived Mesenchymal Stem Cells (2016)
A primary goal in bone tissue engineering is the design of implants that induce controlled, guided, and rapid healing. The events that normally lead to the integration of an implant into bone and determine the performance of the device occur mainly at the tissue-implant interface. Topographical surface modification of a biomaterial might be an efficient tool for inducing stem cell osteogenic differentiation and replace the use of biochemical stimuli. The main goal of this work was to develop micropatterned bioactive silica thin films to induce the osteogenic differentiation of human bone marrow-derived mesenchymal stem cells (hMSCs) only through topographical stimuli. Line and pillar micropatterns were developed by a combination of sol-gel/soft lithography and characterized by scanning electron microscopy, atomic force microscopy, and contact angle measurements. hMSCs were cultured onto the microfabricated thin films and flat control for up to 21 days under basal conditions. The micropatterned groups induced levels of osteogenic differentiation and expression of osteoblast-associated markers higher than those of the flat controls. Via comparison of the micropatterns, the pillars caused a stronger response of the osteogenic differentiation of hMSCs with a higher level of expression of osteoblast-associated markers, ALP activity, and extracellular matrix mineralization after the cells had been cultured for 21 days. These findings suggest that specific microtopographic cues can direct hMSCs toward osteogenic differentiation. © 2016 American Chemical Society.